Nursing pharmacology made incredibly easy! (Incredibly easy, 2013)
Nursing Pharmacology Made Incredibly Easy, Third Edition, doses out pharmacology facts in an easy, reader-friendly style. You'll learn and readily recall such key information as: Pharmacology fundamentals, including where drugs come from and how they're administered and used by the body; Therapeutic classes of drugs to treat all body systems, plus commonly prescribed pain medications, anti-infectives, antineoplastics, and more; Nursing process steps for each drug class; And adverse reactions and potentially dangerous drug interactions